Doxastic wrongs, non-spurious generalizations and particularized beliefs - Fabre, C (Oxford University Press, 2022)
According to the doxastic wrongs thesis, holding certain beliefs about others can be morally wrongful. Beliefs which take the form of stereotypes based on race and gender (or sexual orientation, disability, and so on) and which turn out to be false and are negatively valenced are prime candidates for the charge of doxastic wronging: it is no coincidence that most of the cases discussed in the literature involve false beliefs. My aim in this paper is to show that the thesis of doxastic wrongs does not turn on the truth-value or valence of beliefs.